Head Injuries and Serial Killers: Explore the Link Between Head Trauma and Criminal Behaviour - Melissa Nwako (BJPsych Open)
Aims: This research aims to investigate whether there is a significant correlation between head injuries and the development of violent, repetitive criminal behaviours, particularly serial killers. Examining the neurological and psychological factors associated with head injuries. This study seeks to understand better their influence on criminal tendencies and patterns of behaviour.